Postoperative Hypersensitivity and Digital Radiographic Assessment of a Zinc Modified Versus a Conventional Glass Ionomer Cement in Deep Carious Lesion: Randomized Controlled Clinical Trial (Indian Journal of Public Health Research & Development, 2020)
Aim of the Study: This study aimed to determine the effect of different glass ionomer in the healing of deepcarious lesion after partial caries removalDesign: A total of 50 teeth of patients who fulfilled the inclusion criteriawere selected to participate inthe study. Then they were divided into two main groups: control group (Equia fill) and intervention group(Chemfill rock). Postoperative hypersensitivity (using thermal test and percussion test) and periapical lesions(using digital periapical radiograph) were tested in this period at the baseline (T0), after three months (T3)and after six months (T6).Results: Categorical data were presented as Frequencies (n) and Percentages (%). Fisher’s exact andCochran’s Q tests were used to analyze inter and intra group comparisons respectively. The significancelevel was set at P ? 0.05 for all tests.Conclusion: The hypersensitivity and periapical lesion was no affected by the type of glass ionomerClinical significance: Different type of glass ionomer can be used in deep carious lesion.
Keywords: Deep carious cavities, glass ionomer cement, postoperative hypersensitivity, chem Fil Rock.